Association of IL1R1 Coding Variant With Plasma-Level Soluble ST2 and Risk of Aortic Dissection - Jiang, Wenxi; Wang, Xue; Gao, Pei; Li, Fengjuan; Lu, Ke; Tan, Xin; Zheng, Shuai; Pei, Wang; An, Meiyu; Li, Xi; Hu, Rong; Zhong, Yongliang; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Aortic dissection (AD) is characterized by an acute onset, rapid progress, and high mortality. Levels of soluble ST2 (sST2) on presentation are elevated in patients with acute AD, which can be used to discriminate AD patients from patients with chest pain. sST2 concentrations were found to be highly heritable in the general population. The aim of this study was to investigate the associations of variations in ST2-related gene expression with sST2 concentrations and AD risk. Methods: This case-control study involving a total of 2277 participants were conducted, including 435 AD patients and age- and sex-matched 435 controls in the discovery stage, 464 patients and 943 controls in the validation stage. Eight ST2-related genes were selected by systematic review. Tag single nucleotide polymorphisms (SNPs) were screened out from the Chinese population of the 1000 Genomes Database. Twenty-one ST2-related SNPs were genotyped and plasma sST2 concentrations were measured. Results: In the discovery stage, rs13019803 located in IL1R1 was significantly associated with AD after Bonferroni correction (P=0.0009), and was correlated with circulating sST2 levels in patients with type A AD(AAD) [log-sST2 per C allele increased by 0.188 (95%) CI 0.012-0.366)] but not in type B. Combining the two stages together, rs13019803C was associated with plasma sST2 level in AAD patients [log-sST2 increased by 0.141 (95% CI 0.055–0.227) for per C allele]. Odds ratio of rs13019803 on the risk of AAD is 1.67 (95%CI: 1.33–2.09). Conclusions: The IL1R1 SNP rs13019803C is associated with higher sST2 levels and increased risk of AAD.